Analisa Kekuatan Sambungan Las Tig pada Roll Bar Mobil KMHE dengan Alumunium 6061 Melalui Uji Bending - Elvan Elvan; M. Sobron Yamin Lubis; Steven Darmawan (CV. IRA PUBLISHING, 2025)
The welding process is a production process that aims to combine two types of materials into a usable component. In the manufacturing industry, the Tungsten Inert Gas welding process is widely used in industrial processes requiring high accuracy, good welding quality, and welding results. This study compares the strength of welded joints by varying the welding current. This research uses 6061 aluminum material to determine the strength of Tungsten Inert Gas welding joints. The study focused on the strength of Tungsten Inert Gas welding joints with current variations of 140 A, 160 A, and 180 A using a testing method using a three-point bending test to determine the right current variation in the Tungsten Inert Gas welding process. This study found that the current variation of 160 A with a strength of 203.7 N/mm2 is better than 140 A, 139.9 N/mm2, and 180A, 192.1 N/mm2 in Tungsten Inert Gas welding joints.